A comparative study of Stoppa’s repair versus Lichtenstein technique for surgical management of bilateral inguinal hernia - Patel, Kiran (International Surgery Journal, 2021)
Background: The surgical management of bilateral inguinal hernias has been a point of contention for a long time, particularly in terms of whether to repair them sequentially or simultaneously, especially following tension-free surgeries. The present study was planned to compare the outcomes of bilateral inguinal hernia repair between patients who underwent the Stoppa’s repair and those who underwent Lichtenstein tension free mesh hernioplasty repair. Methods: The study included all patients of both genders with age of 18 years with bilateral inguinal hernias. Patients with following any condition-a complicated inguinal hernia; an obstructed or strangulated inguinal hernia; a recurrent inguinal hernia; previous abdominal surgery; a local skin infection-were excluded from the study. Patients were randomised into 2 groups based on simple randomization-group 1: patients underwent Lichtenstein tension free mesh hernioplasty; and group 2: patient underwent Stoppa’s repair. Results: The operative time was significantly shorter in group 2 patients as compared to group A. In both groups, there were no intraoperative complications. Group 2 patients had significantly lower postoperative pain scores measured by the visual analogue scale at 12 hours postoperatively, but there was no statistically significant difference in pain at 24 hours or 7 days postoperatively. Post-operative hospital stays, return to normal daily activities, and chronic groin pain, there was no statistically significant difference between the two groups. Conclusions: The present study was unable to show that either technique was superior in the treatment of bilateral inguinal hernias. Both procedures, on the other hand, were capable of achieving favourable postoperative outcomes and had similar problems.